Exploration of Copper Oxide Nanoneedle Electrosynthesis Applied in the Degradation of Methylene Blue - Sanchez-Poblete, J; Boulett-Neira, A; Boulett-Neira, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In this study, we report a low cost, fast and unexplored electrochemical synthesis strategy of copper oxide nanoneedles films as well as their morphological and chemical characterization. The nanostructured films were prepared using electrochemical anodization in alkaline electrolyte solutions of ethylene glycol, water and fluoride ions. The film morphology shows nanoneedle-shaped structures, with lengths up to 1–2 µm; meanwhile, high-resolution X-ray photoelectron spectroscopy (HRXPS) and spectroscopy Raman analyses indicate that a mixture of Cu(II) and Cu(I) oxides, or only Cu(I) oxide, is obtained as the percentage of water in the electrolyte solution decreases. A preliminary study was also carried out for the photocatalytic degradation of the methylene blue (MB) dye under irradiation with simulated sunlight in the presence of the nanoneedles obtained, presenting a maximum degradation value of 88% of MB and, thus, demonstrating the potential characteristics of the material investigated in the degradation of organic dyes. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.